The Effectiveness of the Shredder Machine and Empty Fruit Bunch Press to Reduce Oil Losses from Oil Palm Empty Fruit Bunches - Sahrial Hafids; Dewi Fortuna; Ade Rizka Wahyuni (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
The purpose of this study was to determine the effectiveness of the use of "Shredder Machine (SM)" and "Empty Fruit Bunch Press (EFBP) Machine" to reduce oil losses from palm oil empty fruit bunches, as well as analysis of economic aspects. This study used Randomized Block Design (RBD) with two treatments in fifteen groups as replicates. The parameters observed were oil losses, as well as efficiency and effectiveness of SM and EFBP machines, recovery costs, and economic aspects (fixed and variable costs). The result was efficiency (66.82%), effectiveness (91.59%).Assuming 50% of the processed empty bunches can recover oil losses equivalent to Rp 27,215,790 per day or Rp 7,321,047,505 per year. The fixed costwas Rp 629,366,250 and the variable cost was Rp 132,738,534, so the profit from the use of SM and EFBP Machinewas Rp 6,558,942,721 per year.